A study of star formation by Hα emission of galaxies in the galaxy group NGC 4213 - Sakdawoot Maungkorn (2018)
© Published under licence by IOP Publishing Ltd. This research aims to study hydrogen alpha emission, corresponding to star formation of galaxies in the NGC 4213 group that has an average recession velocity of 6,821 km/s. The imaging observations with broad-band filters (B, V and RC) and narrow-band filters ([S II] and Red-continuum) were carried out from the 2.4-m reflecting telescope at Thai National Observatory (TNO). There are 11 sample galaxies in this study, consisting of 2 elliptical, 2 lenticular and 7 spiral galaxies. It was found that the late-type galaxies tend to be bluer than early-type galaxies, due to these galaxies consist of relatively high proportion of blue stars. Furthermore, the equivalent width of hydrogen alpha (EW(Hα)) tends to increase as a function of morphological type. This indicates that star formation in late-type galaxies taking place more than the early-type galaxies. Furthermore, a ratio of the star formation rate to galaxy mass also increases slightly with the galaxy type. This could be due to the interaction between galaxy-galaxy or tidal interaction occurring within the galaxy group.